PEMANFAATAN ANTOSIANIN KULIT UBI JALAR UNGU (Ipomoea batatas L.) SEBAGAI BIOSENSOR KANDUNGAN NATRIUM NITRIT PADA PRODUK DAGING OLAHAN - Rosa Devitria; Mega Elfia; Ynisa Yulan Sarwis (Ensiklopedia of Journal, 2023)
Anthocyanins are one of the natural color pigments in plants that have an important physiological function that can be used as a detector of synthetic substances that exceed the limit, especially the use of sodium nitrite in processed meat. Anthocyanins are found in purple sweet potatoes. Therefore, this study aims to maximize the use of Purple Sweet Potato skin as a biosensor of chemical content in food. This type of research is a descriptive research with quantitative laboratory testing using a UV-Vis spectrophotometer test and a qualitative test using whatmann filter paper No.42 as an indicator. The observed parameter was a discoloration that occurred on whatmann filter paper No.42 before and after dripping the tested sodium nitrite solution. The results showed that the skin of Purple Sweet Potato had anthocyanin levels of 119.56 mg / 100 grams, and from the six samples tested, there was no use of sodium nitrite that exceeded the threshold because after dripping the sample juice occurred a light light purple color on the indicator paper that did not show a discoloration to the positive control dripped sodium nitrite concentration of 5% and 10% which was dark blue. So the results show that purple sweet potato skin anthocyanins have the potential to be developed as natural biosensors for testing the content of chemicals in food, specifically in detecting the use of sodium nitrite that exceeds the threshold in processed meat products.  Keywords:      Anthocyanins, Purple Sweet Potato Skin, Sodium Nitrite, Processed Meats